Studies on the Microflora of Ripe Pawpaw (Carica papaya) Fruits in Ghana (International Journal of Technology and Management Research, 2020)
The aim of the study is to identify fungi associated with fruit rot of pawpaw both in the field and in storage. Three experiments were conducted. In the first experiment, fungi growing on ripe pawpaw fruits randomly collected from plants on the UCC campus were identified in the laboratory. The position on the fruit the fungi appeared was recorded. The second experiment involved the storage of fruits in insect proof containers in the laboratory to indentify fungi growing onthe fruits and the position on the fruit the fungi appeared. In the third experiment, fruits were washed with 10% solution of Milton 2 before they were stored in insect proof containers. Fungi which grew on them and the position on the fruit the fungi appeared were identified. The survey revealed that Collectotricum gloesporiodes which cause anthracnose was the most frequently occurring fungi in the field in the study area. The most serious fungi diseases of pawpaw in storage were found to be anthracnose, stem end rot and black rot which were caused by Collectotricum gloesporiodes, Phomopsis caricae-papayae andPhoma caricae-papayae. It was demonstrated that surface sterilization with 10% Milton 2 solution increased the shelf life of the stored fruits for 2-3 days.Keywords: Carica papaya; Microflora; Milton 2; Surface sterilization; Frequency of occurrence.